The Influence Of Product Differentiation And Price Discounts On Purchasing Decisions At PT. Hindo Medan - Irawan, Dhanni Delyan; Asnawi, Muhammad; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2024)
This study aims to determine and analyze the effect of product differentiation and price discounts on purchasing decisions at PT Hindo Medan. There are still people who think that this store is quite expensive for the price of each product. The product differentiation found in the company is considered to be less effective with other companies and does not have a significant difference. Price Discounts provided are still relatively low compared to discounts from other competing products and consumers cannot decide to shop at this store. This study uses quantitative data types and multiple regression analysis to obtain answers to the research hypothesis, the sample size is 71 respondents, with the sampling technique being a saturated sample. The results of the t test analysis show that there is an effect of product differentiation on purchasing decisions at PT. Hindo Medan can be seen from tcount> ttabel (2.384> 1.667) with a significance of 0.000 <0.05. Price Discount on Purchasing Decisions at PT Hindo Medan can be seen from tcount> ttabel (3,865>1,667) with a significance of 0.001 <0.05 F test together between the Effect of Product Differentiation and Price Discount on Purchasing Decisions at PT Hindo Medan. obtained the value of Fcount> Ftabel (13.365> 3.13) which shows simultaneously the Effect of Product Differentiation and Price Discount on Purchasing Decisions at PT. Hindo Medan It can be seen from the R-square result of 0.282 or 28.2% which indicates that around 28.2 Purchasing Decision variables (Y) can be explained by the Product Differentiation variables (X1 ) and Price Discount (X ).2